Análise multicritério para a priorização de vias urbanas candidatas à requalificação como ruas completas - Pereira, Pedro Henrique dos Santos (2024)
Multimodal streets focusing on active transportation combined with public transport play a crucial role in the pursuit of sustainable urban development. Brazilian cities, such as João Pessoa, lack more effective policies and formal decision-making processes that consider multiple intervening factors and different opinions for the development of a sustainable transportation system. In this sense, the concept of "Complete Streets" and Multi-Criteria Decision Analysis (MCDA) methods are of great value. Therefore, the research aimed to contribute to decision-making processes related to urban transport management, specifically road infrastructure, with a focus on promoting more democratic and equitable roads for different users and modes of transportation. To achieve this, a process for prioritizing road segments for potential requalification as a complete street was proposed using the Analytic Hierarchy Process (AHP), referencing studies conducted in Canada and adapted for the Brazilian city of Recife/PE as well as in Iran. The proposed structure consisted of three objectives and eight criteria, considering: i) the geometric characteristics of the streets, through width and connectivity criteria; ii) circulation and road safety factors, through bus network, cycling network, road safety, and pedestrian flow criteria; and, iii) attractions of the place, through tree coverage and land (street) use criteria. The importance (weights) of the objectives and criteria were defined through consultation with eleven professionals involved in transportation engineering and urban planning. Aggregating individual opinions revealed land use (street) as the most relevant criterion to achieve the overall goal of the work, while the cycle network had the lowest assigned weight. Additionally, considering the proposed structure, data was collected and road segments in four neighborhoods of João Pessoa - Anatólia, Bancários, Castelo Branco, and Jardim São Paulo - were characterized based on the representative attributes of the criteria. This characterization identified some deficiencies in the region, such as a lack of suitable infrastructure for active and public transport and the need for more trees in public circulation spaces to encourage pedestrian flow on the streets. Finally, by aggregating the criterion weight vector with the attributes of the analyzed road segments, it was possible to establish a list of priority segments to receive requalification projects considering the concept of Complete Streets. The list revealed that the priority segments are located on the main road axes, with the majority situated in the Bancários and Castelo Branco neighborhoods.